Personal connections in the digital age: - Baym, Nancy K. (Polity Press, 2015)
The internet and the mobile phone have disrupted many of our conventional understandings of ourselves and our relationships, raising anxieties and hopes about their effects on our lives. In this second edition of her timely and vibrant book, Nancy Baym provides frameworks for thinking critically about the roles of digital media in personal relationships. Rather than providing exuberant accounts or cautionary tales, it offers a data-grounded primer on how to make sense of these important changes in relational life